Professional Realization of the Graduate Students of Department “Economic Sociology” - Kineva, Todorka (Research Papers, 2018)
The main goal of this paper is to determine the professional realization of the graduates with Bachelor’s degree of the Department of Economic Sociology in UNWE. The tasks for achieving the goal are related to the presentation of the capacity of the department in the preparation of specialists (sociologists and economists) and analysis of results from an empirical sociological survey “Professional realization of graduates of the Department of Economic Sociology”. Two methods for registering the information are used – an empirical inquiry and research of documents. Training is a key prerequisite for professional realization in the specialty.